European Railway Review / Celebrating over 20 Years of Working Together in Rail - Waters Craig (European Railway Review, 2016)
Sweden's Plans to Benefit Future Generations, Strengthening the Railway is Essential for Sustainable and Efficient Transport, The Future of Train Travel for SJ, Railway 2050, MTR Builds on Its Strong Reputation, Internet of Trains - How Digitisation Creates New Value Opportunities, Trafikverket: Lowering Market Entry Barriers, A New Challenge for ERTMS/ ETCS Level 2 on Italian Conventional Lines, InnoTrans 2016.